Astrocytic FABP5 mediates retrograde endocannabinoid transport at central synapses - Saida Oubraim; Mohammad Fauzan; Keith Studholme; Chris Gordon; Sherrye T. Glaser; Roh-Yu Shen; Iwao Ojima; Martin Kaczocha; Samir Haj-Dahmane (iScience)
Summary: Endocannabinoids (eCBs) regulate synaptic function via cannabinoid receptors. While eCB signaling is well understood, the mechanisms underlying eCB synaptic transport are poorly characterized. Using 2-arachidonoylglycerol (2-AG)-mediated depolarization-induced suppression of inhibition (DSI) in the hippocampus as a readout of retrograde eCB signaling, we demonstrate that the deletion of fatty acid binding protein 5 (FABP5) impairs DSI. In FABP5 KO mice, DSI was rescued by re-expressing wild-type FABP5 but not an FABP5 mutant that does not bind 2-AG. Importantly, the deletion of astrocytic FABP5 blunted DSI, which was rescued by its re-expression in the astrocytes of FABP5 KO mice. Neuronal FABP5 was dispensable for 2-AG signaling. DSI was also rescued by expressing a secreted FABP5 variant but not by FABP7, an astrocytic FABP that does not undergo secretion. Our results demonstrate that extracellular FABP5 of astrocytic origin controls 2-AG transport and that FABP5 is adapted to coordinate intracellular and synaptic eCB transport.